The LOFAR tied-array all-sky survey (LOTAAS): Characterization of 20 pulsar discoveries and their single-pulse behaviour. Issue 1 (23rd October 2019) - Michilli, D; Bassa, C; Cooper, S; Hessels, J W T; Kondratiev, V I; Sanidas, S; Stappers, B W; Tan, C M; van Leeuwen, J; Cognard, I; Grießmeier, J-M; Lyne, A G; et al.
ABSTRACT: We are using the LOw-Frequency ARray (LOFAR) to perform the LOFAR Tied-Array All-Sky (LOTAAS) survey for pulsars and fast transients. Here, we present the astrometric and rotational parameters of 20 pulsars discovered as part of LOTAAS. These pulsars have regularly been observed with LOFAR at 149 MHz and the Lovell telescope at 1532 MHz, supplemented by some observations with the Lovell telescope at 334 MHz and the Nançay Radio Telescope at 1484 MHz. Timing models are calculated for the 20 pulsars, some of which are among the slowest spinning pulsars known. PSR J1236 − 0159 rotates with a period P ∼ 3.6 s, while five additional pulsars show P > 2 s. Also, the spin-down rates P are, on average, low, with PSR J0815 + 4611 showing P 4× 10^-18 . Some of the pulse profiles, generically single-peaked, present complex shapes evolving with frequency. Multifrequency flux measurements show that these pulsars have generically relatively steep spectra but exceptions are present, with values ranging between ∼−4 and −1. Among the pulsar sample, a large fraction shows large single-pulse variability, with four pulsars being undetectable more than 15 per cent of the time and one tentatively classified as a Rotating Radio Transient. Two single-peaked pulsars show drifting sub-pulses.